The Triglycerides and Glucose Index rather than HOMA-IR is more associated with Hypogonadism in Chinese men. Issue 1 (December 2017) - Zhang, Kun; Chen, Yi; Liu, Lijie; Lu, Meng; Cheng, Jing; Gao, Fengbin; Wang, Ningjian; Shen, Zhoujun; Lu, Yingli
Abstract Previous studies have reported that insulin resistant and low testosterone are related. The triglyceride and glucose index (TyG) well mirrors insulin sensitivity. No study investigated the application of TyG in male hypogonadism. We aimed to explore whether TyG was associated with hypogonadism, and also evaluate the ability of TyG compared to HOMA-IR as a possible hypogonadism predictor. A total of 4299 male subjects were enrolled from 22 sites in East China. Hypogonadism was defined as total testosterone <11.3 nmol/L. 695 (16.2%) hypogonadal men had significantly higher TyG index. The prevalence of hypogonadism stepwise increased across increasing TyG quartiles (P < 0.01). TyG was negatively associated with sex hormones and hypogonadism after adjustment for age, current smoking status, hypertension and overweight/obesity (all P for trend <0.01). The full-adjusted odds ratio was 6.1 for the highest quartile compared with the lowest quartile of TyG (95% CI 4.51, 8.25, P < 0.001). On ROC curve analysis, a larger area under the curve was found for TyG (0.71, 95% CI 0.69, 0.73) than for HOMA-IR (0.68, 95% CI 0.66, 0.70). Thus, the TyG was significantly associated with a higher prevalence of hypogonadism in Chinese men. TyG had a better predictive power for hypogonadism than HOMA-IR.